2022
DOI: 10.5812/ijcm.113715
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin Is a Promising Sensitizer for Dual-Frequency Sono-photodynamic Therapy in Mice Breast Cancer

Abstract: Background: The combination of sonodynamic and photodynamic therapy (SPDT) may be a new hopeful non-invasive method for cancer treatment, which incorporates a combination of low-intensity ultrasound, laser radiation, and a sensitizer agent. Objectives: This study aimed at evaluating the effects of hematoporphyrin (HP)-mediated SPDT (dual-frequency ultrasound and laser radiation) in the management of mice breast adenocarcinoma. Methods: One hundred and thirty-two female mice with implanted tumors were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Different implementations of multi-frequency ultrasound are also summarized, including single-element transducer, double transducers, triple transducers and phased array transducers, each with its own specialty and favored for particular tasks. Benefited from lesion size control, cavitation enhancement, low power needs and multi-foci treatment, this technique offers a wide range of applications, including: sonothrombolysis, tissue (tumor) ablation, sonodynamic treatment, sonochemical treatment, temperature rise, cell differentiation, BBB opening, transdermal drug delivery, sub-harmonic imaging enhancement and split-focus treatment [2] , [6] , [7] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [22] , [23] , [25] , [28] , [30] , [32] , [33] , [36] , [50] , [51] , [53] , [54] , [55] , [60] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [23] , [75] . Moreover, this review discusses about the decisive parameters for multi-frequency treatment and suggests guidelines for parameter selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different implementations of multi-frequency ultrasound are also summarized, including single-element transducer, double transducers, triple transducers and phased array transducers, each with its own specialty and favored for particular tasks. Benefited from lesion size control, cavitation enhancement, low power needs and multi-foci treatment, this technique offers a wide range of applications, including: sonothrombolysis, tissue (tumor) ablation, sonodynamic treatment, sonochemical treatment, temperature rise, cell differentiation, BBB opening, transdermal drug delivery, sub-harmonic imaging enhancement and split-focus treatment [2] , [6] , [7] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [22] , [23] , [25] , [28] , [30] , [32] , [33] , [36] , [50] , [51] , [53] , [54] , [55] , [60] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [23] , [75] . Moreover, this review discusses about the decisive parameters for multi-frequency treatment and suggests guidelines for parameter selection.…”
Section: Discussionmentioning
confidence: 99%
“…The process of bubble collapsing and consequent effects is called inertial cavitation. A wide range of studies have reported the enhanced cavitation by multi-frequency ultrasound, such as lesion enlargement and thrombolysis enhancement [11] , [22] , [23] . However, the mechanism behind is still poorly understood, although various experimental and theoretical studies have shed light on the advancement of this technology [24] .…”
Section: Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations